Flexible urea biosensor based on CuS/Bioglass 45S5.TiO2 Nps thin films - Carrillo, Amanda (2024)
Chronic renal insufficiency has been a high-incidence disease around the world in recent years. With the lack of devices to detect these illnesses opportunely, developing urea biosensors is imperative. This work reports the application of copper sulfide (CuS) thin films deposited via a chemical bath and Bioglass 45S5/titanium dioxide nanoparticles thin films in a urea flexible biosensor. The Bioglass 45S5 was deposited over CuS and applied onto polyethylene naphthalate (PEN) and polyethylene terephthalate (PET) with indium tin oxide (ITO) substrates. The systems PEN/CuS/Bioglass 45S5.TiO2 NpS and PET/ITO/CuS/ Bioglass 45S5.TiO2 were characterized optically by UV-Vis. The CuS presented an absorption border around 600 nm and a decrease in transmittance percentage by adding Bioglass. Scanning Electron Microscopy carried out the microstructural characterization; both systems displayed a porous morphology featuring channels suitable for immobilizing the enzyme. The sensors showed a resistive behavior based on the current-voltage curve. The urease enzyme was immobilized by adsorption. The optical changes after adding urease were measured by UV-Vis, obtaining ammonia from the reaction between urease and urea, showing an absorption border around 850 nm. Changes in urea concentrations between 1 and 10 mM caused an increase in resistivity in both samples, obtaining a sensitivity of 12.887 kΩ/sq/mM and 12.411 kΩ/sq/mM, and a linearity of 0.9946 % and 0.9601 % for the samples deposited over PEN and PET ITO, respectively. A Cole-Cole plot showed a behavior corresponding to an equivalent circuit composed of a parallel combination of a resistor and a capacitor in series with a phase constant element; this latter could be attributed to the measurement electrodes. Each sensor was implemented in a Wheatstone bridge. A voltage decrease was obtained for the sample deposited over PET ITO, with a sensitivity of −102.7 mV/mM, and a voltage increase was obtained in the sample deposited over PEN, with a sensitivity of 30.5 mV/mM.